Stroke risk in patients with asymptomatic carotid atherosclerosis: should it be treated medically or surgically? - Moreno Muñoz, Roberth Nixon (2023)
Cerebrovascular disorders remain the leading cause of neurological morbidity and mortality in the world, representing one of the pathological entities responsible for the greatest burden of disease worldwide. Carotid atherosclerosis or stenosis is a potential risk factor for ischemic stroke. The identification and strict follow-up of this condition are essential in the secondary prevention of complications through primary care and the specialized treatment of cardiometabolicrisk. However, depending on this risk and/or presence of symptoms, definitive treatment is necessary. Currently, there is controversy as to whether asymptomatic carotid stenosis is better to be treated medically or surgically. Consideringthe significance of such entity, this review aims to analyze recent evidence on the risk of ischemic stroke in the case of asymptomatic carotid atherosclerosis among adults, as well as the potential benefit of the surgical vs. pharmacologicaltreatment for this condition. For this purpose, a literature search for publications up to 2023 was carried out in PubMed, ScienceDirect, Web of Science and MEDLINE databases. It was shown that there is a significant risk of stroke associated with asymptomatic carotid stenosis (> 10 % approximately), even in patients with active antiplatelet and lipid-lowering therapy. Out of all those who receive medical treatment, around 80 % had a five-year survival rate. However, stenosisprogression occurs on average in more than 60 % of the cases and is significant. On the other hand, carotid stenting and endarterectomy are curative interventions. Nevertheless, these procedures involve a higher risk compared to the medicaltherapy during the peri- and postoperative period, as well as 30 days afterwards, due to the occurrence or recurrence of stroke, acute myocardial infarction or death from any cause. Despite this, the use of endarterectomy has shown superiorlong-term benefits concerning these same outcomes. Thus, evidence regarding the superiority of surgical treatment compared to pharmacological treatment for asymptomatic carotid atherosclerosis or stenosis is heterogeneous. However, it seems that surgical treatment, specifically endarterectomy, could have a significant impact on the occurrence orrecurrence of ipsilateral stroke and death in the long term but with controversial peri- and postoperative outcomes.